AAV-mediated NT-3 overexpression protects cochleae against noise-induced synaptopathy. Issue 4 (July 2018) - Chen, Hengchao; Xing, Yazhi; Xia, Li; Chen, Zhengnong; Yin, Shankai; Wang, Jian
Abstract The synapse between inner hair cells (IHCs) and type I spiral ganglion neurons (SGNs) has been identified as a sensitive structure to noise-induced damage in the mammalian cochlea. Since this synapse provides the major information pathway from the cochlea to the auditory brain, it is important to maintain its integrity. Neurotrophin-3 (NT-3) has been known to play an important role in the development and the functional maintenance of this synapse. Application of exogenous NT-3, or overexpression of this gene in a transgenic animal model, have shown the value to protect this synapse from noise-induced damage. In the present study, NT-3 overexpression was induced by cochlear gene transfection before noise exposure via the use of an adeno-associated viral (AAV) vector. We found that such an overexpression provided a significant synaptic protection against a noise exposure that caused massive damage to the synapses, likely due to it promoting the repair of the synapse after the initial damage.